Hydrogen Bonds Involving Cavity NH Protons Drives Supramolecular Oligomerization of Amido‐Corroles. Issue 42 (6th July 2017) - Orłowski, Rafał; Tasior, Mariusz; Staszewska‐Krajewska, Olga; Dobrzycki, Łukasz; Schilf, Wojciech; Ventura, Barbara; Cyrański, Michał K.; Gryko, Daniel T.
Abstract: trans ‐A2 B‐Corroles with amide substituents at different positions versus the macrocyclic core have been synthesized. Their self‐organizing properties have been comprehensively evaluated both in solid‐state and in solution. The rigid arrangement of the amide functionality with the corrole ring led to the formation of strong intramolecular interactions and precluded intermolecular interactions. Replacement of sterically hindered C6 F5 substituents at positions 5 and 15 with smaller electron‐withdrawing CO2 Me groups resulted in significant changes in the self‐assembly pattern. With these substituents, tetramers formed in a crystalline state, in which one of the H‐pyrrole subunits is out of the corrole plane. This allows the N‐H group to form a hydrogen bond with a neighboring carbonyl group of the n ‐butyl amide fragment. DOSY NMR studies showed that amido‐corroles bearing the OCH2 CONH n Bu motif formed dimers in millimolar solutions in nonpolar solvents and the dimers existed in equilibrium with monomers. However, the corroles possessing meso ‐ester groups did not form dimers in polar tetrahydrofuran. Comprehensive optical studies allowed the absorption and emission features of the monomer corroles to be characterized in dilute solutions. Abstract : Organizing corroles : For trans ‐A2 B‐corroles possessing amide substituents, a short tether between the amide moiety and the core facilitates hydrogen‐bond formation, but only in the intramolecular mode, whereas a flexible linker drives supramolecular oligomerization in the solid state and a dimerization in nonpolar solvents (see figure). The presence of two CO2 Me groups at positions 5 and 15 results in formation of tetramers in the crystalline state.